Vacunas contra el dengue y estado de la vacunación en Perú y Latinoamérica - Quispe-Vicuña, Carlos (2024)
Due to the recent increase of dengue cases in Latin America, preventive measures beyond vector control or community participation are needed. In this regard, the use of vaccines has emerged as a promising tool. To date, there are three vaccines in phase III clinical trials: CYD-TDV, TAK-003 and Butantan-DV, all showing high efficacy and safety. Several Latin American countries have started implementing vaccination programs with TAK-003 (Qgenda®) vaccine since 2023. Brazil has initiated vaccination programs in children aged 10-14 years and Argentina has implemented TAK-003 vaccine in the private sector. In Peru, despite recent outbreaks of dengue, vaccination has not been considered in the national dengue plan. Although its incorporation represents a public health challenge, we believe that the vaccine would be useful in limiting severe cases and mortality from this disease.